Anti-XA Assay Is a Poor Predictor of Direct Oral Anticoagulant Interference in Lupus Anticoagulant Tests. (21st September 2018) - Guarner, Jeannette; Maier, Cheryl; Ingle, Ann; Stowell, Sean; Roback, John D; Duncan, Alexander
Abstract: Background: The effect of direct oral anticoagulants (DOACs) on lupus anticoagulant (LAC) testing has been widely publicized. This effect is evident when the Dilute Russell Viper Venom Time (DRVVT) and Silica Clotting Time (SCT) screens cannot be confirmed, which necessitates mix and mix/confirm studies. In addition to the DRVVT and SCT screen/confirm tests and, when necessary, mixing studies, we also perform an anti-Xa assay to aid in interpretation. Objective: We sought to determine whether the anti-Xa assay could predict the effect of DOACs on LAC tests. Method: We conducted a 3-month retrospective chart review of cases with anti-Xa results >0.2 U/mL. Results: During the study period, a total of 352 specimens were tested. Anti-Xa activity >0.2 U/mL was present in 69 (19.6%) specimens. Of these, 14 samples were negative for all LAC tests, including 3 from patients receiving DOACs, while the rest were from patients on enoxaparin, heparin, or warfarin. Twenty-one patients had positive screen/confirm tests, with or without identified antibodies, 18 of whom were on a DOAC (rivaroxaban). Ten patients with positive antibodies had negative screen/confirm tests, including 5 on a DOAC (apixaban) and 5 on enoxaparin. Nineteen patients had evidence of anticoagulation primarily with DRVVT testing and, except for 3 patients on heparin, all others were on DOAC. Lastly, there were 5 patients who showed positive screen/confirm tests for DRVVT (n = 4) or SCT (n = 1) with evidence of a DOAC on the other test (4 on SCT and 1 on DRVVT), 3 of whom were on rivaroxaban and 2 on apixaban. Of the 69 specimens with anti-Xa >0.2 U/mL, 19 (27%) showed presence of a DOAC (DRVVT or SCT could not be confirmed). Conclusion: Although DOAC therapy affects the DRVVT or SCT in a number of specimens, over 70% may still show the LAC effect. Anti-Xa >0.2 U/mL is not helpful at predicting which samples will show the DOAC effect.